2022
DOI: 10.1108/imds-04-2021-0247
|View full text |Cite
|
Sign up to set email alerts
|

Advertising and pricing of online direct selling considering network externalities

Abstract: PurposeConsidering the network externalities of online selling, this paper builds three different online direct selling models: manufacturer direct selling (MN model), network platform direct selling (NN model) and retailer direct selling (RN model). The optimal advertising and pricing decision and corporate profits under each selling model are investigated.Design/methodology/approachCombining the characteristics of online direct selling, this paper formulates direct selling models that are dominated by differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
(85 reference statements)
1
3
0
Order By: Relevance
“…As network externalities intensify, the manufacturer can gain profits through higher sales prices and enhanced recycling service. This aligns with the conclusions corroborated by Shen et al (2023).…”
Section: Manufacturer Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…As network externalities intensify, the manufacturer can gain profits through higher sales prices and enhanced recycling service. This aligns with the conclusions corroborated by Shen et al (2023).…”
Section: Manufacturer Modelsupporting
confidence: 92%
“…Yang et al (2023c) examined the impact of network externality on manufacturers' R&D investment and the introduction of new products, highlighting that a rise in network externalities might reduce manufacturer profitability. Meanwhile, Shen et al (2023) investigated pricing and advertising decisions within the online direct sales model, indicating that network externalities are conducive to the development of e-commerce enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aoyagi (2018) found that when the strength of NE increases linearly with the sales volume of products, the market may be monopolized by enterprises, and only the two-part pricing strategy can be robust under the disturbance of linear NE. NE has more obvious influence on dominant supply chain members (Shen et al, 2022). The intensity of the delayed network effect and quality differential affect product marketing strategies (Kong et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…NE is essentially a demand‐side scale economy, which means that the utility of consumers increases as more consumers purchase the same or compatible products (services) (Katz & Shapiro, 1985; Kong et al, 2022). Obviously, NE can influence purchasing decisions made by consumers by influencing their expectations of the market scale of products (Shen et al, 2022). The emergence of NE means consumer purchase decisions are influenced by the strength of NE and the expected demand of product.…”
Section: Introductionmentioning
confidence: 99%